Minimal adverse outcomes of postnatal cytomegalovirus infection in term or moderate and late preterm infants - Chen, Jie; Zhou, Yineng; Tang, Jie; Xu, Chenyu; Chen, Liping; Xu, Biyun; Dai, Yimin; Hu, Yali; Zhou, Yi-Hua (Frontiers in Pediatrics, 2023)
Objective: The aim of study was to investigate at what extent breastfeeding and vaginal delivery can increase mother-to-child transmission of cytomegalovirus (CMV) and to observe the clinical outcomes of postnatal infection in term or moderate and late preterm infants. Methods: In this retrospective study of prospectively collected clinical data and serum samples, during 2012‒2015, 380 women with CMV IgG positive/IgM negative and their 384 infants (4 twin pairs) with gestational age ≥32 weeks were included. CMV IgG and IgM were measured with enzyme-linked immunosorbent assay. Results: Of 384 infants followed up at 10.2 ± 2.3 months age, 177 (46.1%) were defined with CMV infection based on the presence of higher CMV IgG levels than in their mothers. The infection rate in 190 breastfed infants was higher than in 194 formula-fed infants (62.6% vs 29.9%, P <0.001). Vaginally delivered infants (172) had higher CMV infection rate than 212 infants delivered by caesarean section (55.2% vs. 38.7%, P = 0.001). Compared with formula feeding and caesarean section, breastfeeding and vaginal delivery increased postnatal CMV infection respectively (OR = 3.801, 95% CI 2.474‒5.840, P <0.001; OR = 1.818, 95% CI 1.182‒2.796, P = 0.007). Nevertheless, compared to uninfected infants, CMV-infected infants had comparable height and body weight and showed no adverse effect on the liver enzymes. Conclusion: Breastfeeding and vaginal delivery can increase postnatal CMV infection; however, the infection does not influence the growth of the term infants or preterm infants with gestational age ≥32 weeks. Thus, breastfeeding should be encouraged in these infants regardless of maternal CMV IgG status.